The Role of Positive Framing in the Relationship between Career Commitment and Career Success - James, R. (My University, 2020)
Individual-level resources that energize individuals have become more critical than before for career success. This study aims to investigate the influence of career commitment on career success and the moderating role of positive framing on the relationship between career commitment and career success. This study included 159 responses drawn from private financial institutions in Sri Lanka. This study adopted a quantitative approach and employed hierarchical multiple regression to analyze the data. The results indicated that respondents' profile data did not significantly influence career success, but career commitment and positive framing positively influence career success. Further, this study explored that employees' engagement in positive framing moderate the relationship between career commitments and career success, it indicates that this relationship is more vital for those who engage in a high level of positive framing than those who engage in the low level of positive framing. Career commitment and positive framing together explain 60% of the variance in career success. This is the first study that examines the subject of positive framing on the relationship between career commitment and career success. By identifying the moderator role of positive framing, this study extends our understanding of the role of positive framing in career research. This study suggests the significant role of individuals in their career success. The results of this study advise the employees to develop their personal career goals and involve in these goals. In addition to the career commitment, employees are advised to develop their self-management process in an optimistic way to achieve their career success.
Keywords: Self-management; Positive Framing; Career; Career Commitment; Career Success